Emerging ionic liquid-based techniques for total-metal and metal-speciation analysis - Martinis, Estefanía Mabel (2010)
Ionic liquids (ILs) are generally considered to be more environmentally friendly than common organic solvents and have unique characteristics (e.g., effectively no vapor pressure, adjustable viscosity and miscibility in aqueous phases). They are also considered to be highly efficient extractant phases to improve analyte selectivity and sensitivity, so that they are important tools for chromatographic and spectrometric analysis. We review state-of-the-art applications of ILs in analytical chemistry with special emphasis on metal determination and speciation analysis. We discuss modern microextraction techniques based on ILs [e.g., dispersive liquid-iquid microextraction (DLLME), singledrop microextraction (SDME), and on-line LLME]. Also, we comment on potential applications and developments of solid-phase extraction (SPE) techniques involving IL-modified surface materials for metal retention and preconcentration. In all cases, we review crucial parameters and practical considerations of method optimization and application. Further, we critically compare IL-based methods in terms of analytical performance and environmental compatibility.